"They just don't care about us!": Police custody experiences for young men with histories of injecting drug use. Issue 1 (March 2020) - Walker, Shelley; Higgs, Peter; Stoové, Mark; Wilson, Mandy
Young men (aged 18–24) represent a quarter of all episodes of police custody detention for adult males in Victoria, Australia. Despite this, little is known about their experience. Using Bacchi's Foucauldian-influenced "What's the problem represented to be?" approach and data from interviews with 28 young men with histories of injecting drug use who were detained in police custody prior to adult prison, we aim to address this gap in the literature. We highlight how dividing practices of discrimination made possible their subjectification as "dangerous violent Others" and how unruly behaviour and self-harm were simultaneous mechanisms for voicing their despair and frustration, for gaining power in a place in which they had very little control and for resisting dominant truths imposed upon them as worthless subjects. It is such positioning we argue, that allowed the forfeiting of their rights to basic health care, fair treatment and respect, and at the same time produced and exacerbated a range of psychological, physical and social harms. Our analysis raises important questions about police custody, notably its role in the production of inequality and further marginalisation of vulnerable groups.